2014
DOI: 10.1177/0267323114545722
|View full text |Cite
|
Sign up to set email alerts
|

More national less European? The comparison of the last two general elections in Turkey

Abstract: This article will examine how the media reported the 2011 election campaign in Turkey in comparison to the 2007 elections. In order to reflect the different ideological segments within the society (pro-secular, nationalist vs religious-conservative), four newspapers – Zaman, Cumhuriyet, Hürriyet and Posta – are chosen. The empirical evidence suggests that there are similarities between the analysis of the 2011 elections and the previous research findings of the 2007 elections with regard to the topics garnered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…In a more recent study on the 2011 Turkish elections, Çarkoğlu et al (2014) confirmed earlier findings of high press–party parallelism in terms of major Turkish newspapers’ political favouring of either AKP or Cumhuriyet Halk Partisi (Republican People’s party (CHP)). Toker (2015) had similar findings from comparing media coverage of the 2007 and the 2011 elections. Against this backdrop of increased press–party parallelism, this study explores the differential coverage of the political crisis due to the corruption probe in terms of the different frames that three competing media outlets preferred to adopt.…”
Section: Turkey’s Polarized Media Systemsupporting
confidence: 53%
“…In a more recent study on the 2011 Turkish elections, Çarkoğlu et al (2014) confirmed earlier findings of high press–party parallelism in terms of major Turkish newspapers’ political favouring of either AKP or Cumhuriyet Halk Partisi (Republican People’s party (CHP)). Toker (2015) had similar findings from comparing media coverage of the 2007 and the 2011 elections. Against this backdrop of increased press–party parallelism, this study explores the differential coverage of the political crisis due to the corruption probe in terms of the different frames that three competing media outlets preferred to adopt.…”
Section: Turkey’s Polarized Media Systemsupporting
confidence: 53%
“…The link between alternative/community media and organizations within the sphere of civil society is especially important due to the politically polarized media environment in Turkey (Toker 2015). Scholars studying the relationship between media and democracy in Turkey suggest that the Turkish media environment resembles a 'neoliberal media autocracy' in which 'profit rather than journalistic ideals' (Akser and Baybars-Hawks 2012: 304) is considered important and 'print and broadcast media reporters continually feel pressured toward self-censorship' (Akser and Baybars-Hawks 2012: 309).…”
Section: Social Movements and Alternative/community Mediamentioning
confidence: 99%
“…Through its news coverage and framing, the media cause a "change in the standards that people use to make their evaluations" (Iyengar and Kinder, 1987: 63). There is consensus on the relationship between news coverage of current events and their impact in shaping public opinion (KhosraviNik, 2010;Kokkonen, 2017;Kolukırık, 2009;Doğanay et al, 2018, Toker, 2004, especially if a sparse 'information environment' presents a biased message that can easily cultivate certain attitudes and create expectations about a particular issue (Gerbner et al, 2002;Vergeer et al, 2000, Toker, 2015.…”
Section: Introductionmentioning
confidence: 99%